The CO2 electrolysing mechanism in single-phase mixed-conducting cathode of solid oxide cell - Zhu, Zidi; Jiang, Yunan; Zhang, Lijie; Han, Hairui; Li, Aijun; Xia, Changrong (Frontiers in Chemistry, 2024)
In the field of solid oxide cells (SOC), unveiling the electrochemical reaction and transfer mechanisms in mixed ionic and electronic conducting (MIEC) electrodes is of great importance. Due to the chemical capacitance effects of MIEC materials, SOC often shows large capacitance current during electrochemical tests, which might interfere with the polarization behaviors. This work presents a numerical multiphysical model based on the transport of oxygen species, which accurately and concisely replicates the current-voltage curves of a solid oxide electrolysis cell (SOEC) with MIEC electrodes under various scanning rates. For the first time, the scanning IV method and EIS method on SOEC are integrated, enabling the separation of Faraday and charging currents. Thus, both the bulk diffusion and surface adsorption/desorption processes of the oxygen species are encompassed, which explains how the current being generated due to intertwined chemical capacitance effects and chemical reactions in the MIEC electrodes.